Premature ejaculation and quality of life among men attending Klinik Kesihatan Jaya Gading, Kuantan - Zulkifli Harun,; Saharuddin Ahmad, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Premature ejaculation (PE) is an important sexual problem among men attending health clinic. Impacts of this condition towards quality of life still require further exploration. Aims of the study is to determine the proportion and determinants for PE and its impact on Quality of Life (QOL) among men attending a public health clinic in Kuantan Methods A cross-sectional study involving 290 respondents was conducted at a public health clinic over the period of five months (Nov 2015-March 2016). A validated self-administrated questionnaire that consisted of socio-demographic questionnaire, clinical characteristics, premature ejaculation diagnostic tool (PEDT) and WHO quality of life (WHOQOL-BREF) were used. Results The proportion of PE was 33.9% with PE 18.1% (49/271) and probable PE 15.8% (43/271). Multivariate analysis showed that level of education (p=0.002, OR 3.281/95% CI 1.183, 9.101) and hypertension (p=0.047, OR 1.788/95% CI 1.008, 3.170) were the only significant predictors for PE after controlling self-reported erectile dysfunction, pulmonary and neurological disorder. PE patients had lower median scores QOL in all four domain namely physical health, psychological, social relationship, environment (all domains with p<0.001). Conclusions The proportion of men diagnosed with premature ejaculation in this study is high and possibly associated with level of education and hypertension. Men with PE had lower quality of life in domains of physical health, psychological, social relationship and environment. Hence, it is recommended for PE screening among male attendees to primary health clinic especially those with hypertension and moderate level of education.